Prasasti Horrn: Tinjauan Epigrafis - Akbarulhuda, Isa; Rahayu, Andriyati (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2023)
Horrn inscription is a copper plate inscription found in Kediri that is often associated with Perang Bubat in the Majapahit era. Horrn Inscription doesn’t mention chronology or the king’s name, it makes some researchers have different ideas about Horrn inscription, therefore this study is important to reexamine this inscription. This study aims to know the relative chronology of the Inscription of Horrn and composea historical story with newer data and research. The method used in this study is the epigraphy method. The result of this study is that the inscription of Horrn was not from the Majapahit era, but from the Garasakan era around 1050 D.C and copied in the Majapahit era. The event written in the Horrn inscription showed an enemy invasion from Sunda to Horrn village. The enemy from Sunda refers to Samarawijaya, King of Panjalu, a descendant of Dharmawangsa Tguh. Another result of this study supports the statement from Boechari and Anggoro that the Horrn inscription was promulgated at the same time as Mapanji Garasakan’s era.